Sam Vernon, Rage Wave. (1st June 2019) - Handley-Derry, Elizabeth
Sam Vernon, Rage Wave Curated by Olivia K. Young, Gallery 44 Center for Contemporary Photography, Toronto January 12 – February 10, 2018